Failure of Lightweight Aggregate Concrete in Compression under Stress Gradients - Zivkovic Jelena; Øverli Jan Arve (Nordic Concrete Research, 2019)
The objective of this experiment is to investigate the behaviour of lightweight aggregate concrete (LWAC) under compression and with stress gradients. Experimental program contained three sets of LWAC which were used for production of 21 prisms. Lightweight aggregate argillite slate, called Stalite, from North Carolina had been used. The sets differed in using dry (0.10% moisture content) or saturated (7.9% moisture content) aggregate. The third set included a small amount of polyvinyl alcohol fibres (PVA). The geometry of the prisms were 100 × 140 × 480 mm (width × length × height). Prismatic samples were loaded centrically and eccentrically in compression.